2014
DOI: 10.1371/journal.pone.0103711
|View full text |Cite|
|
Sign up to set email alerts
|

Large-Scale Wind Disturbances Promote Tree Diversity in a Central Amazon Forest

Abstract: Canopy gaps created by wind-throw events, or blowdowns, create a complex mosaic of forest patches varying in disturbance intensity and recovery in the Central Amazon. Using field and remote sensing data, we investigated the short-term (four-year) effects of large (>2000 m2) blowdown gaps created during a single storm event in January 2005 near Manaus, Brazil, to study (i) how forest structure and composition vary with disturbance gradients and (ii) whether tree diversity is promoted by niche differentiation re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
160
0
5

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 92 publications
(173 citation statements)
references
References 101 publications
(191 reference statements)
8
160
0
5
Order By: Relevance
“…It should be emphasized that the interaction of wind and trees is nonlinear and involves complex processes and the integration of disciplines such as soil science, physiology, ecology, biomechanics, and meteorology [6,11,83,84]. Wind, wind loading, gusts of winds, tree stature, tree species (and associated characteristics such as tree crown shape and density, root architecture and shape, and wood density), topography, soil, cumulative processes, etc.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It should be emphasized that the interaction of wind and trees is nonlinear and involves complex processes and the integration of disciplines such as soil science, physiology, ecology, biomechanics, and meteorology [6,11,83,84]. Wind, wind loading, gusts of winds, tree stature, tree species (and associated characteristics such as tree crown shape and density, root architecture and shape, and wood density), topography, soil, cumulative processes, etc.…”
Section: Discussionmentioning
confidence: 99%
“…Wind, wind loading, gusts of winds, tree stature, tree species (and associated characteristics such as tree crown shape and density, root architecture and shape, and wood density), topography, soil, cumulative processes, etc. all play a role in the production of windthrows [11,[83][84][85][86][87][88] resulting in tree failure at a lower wind speed than expected [1,3]. Amazonia covers about 5.3 million km 2 , and has many environmental and functional gradients [89,90].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results indicate that in central Amazon terra firme forests, vegetation dynamics can also influence soil attributes at the landscape level. In this region, the observed organic carbon enrichment derived from widespread tree mortality might also be related to the fast establishment and growth of pioneer species in heavily disturbed areas (Chambers et al, 2009;Marra et al, 2014).…”
Section: Intensity Of Disturbance and Soil Carbon Stocksmentioning
confidence: 97%
“…The widespread tree mortality creates canopy gaps with a wide range of sizes (from few square meters up to thousands of hectares; Nelson et al, 1994;Negrón-Juárez et al, 2010 and affects forests at the landscape level . It has been reported that these large gaps have a potential effect on carbon cycling (Chambers et al, 2013) and can promote tree species diversity by allowing a diverse cohort of species with a broad range of life history strategies (Chambers et al, 2009;Marra et al, 2014) and allometry .…”
Section: Introductionmentioning
confidence: 99%